Climate Trends and Impacts in China - Sall, Chris (World Bank, Washington, DC, 2014)
This discussion paper summarizes observed and projected trends in extreme weather events, present-day climate variability, and future climate change and their impacts on China's different regions. Findings are presented from China's national assessment report on climate change (2007) and second national assessment report on climate change (2011) as well as other studies by Chinese and international experts. In addition to reviewing the physical climate science, the paper also looks at trends in economic damages in China from weather related hazards. The paper serves as background for a series of discussion papers on climate risk management and adaptation in China. The growing body of scientific evidence shows that China's climate is indeed changing, especially when climate is viewed at the regional level. Temperatures are rising, precipitation regimes are changing, and shifts have occurred in the distribution of extreme weather events. The effects of extreme weather events, present-day climate variability, and future climate change cut across many different sectors of China's economy. China's government estimates that direct economic losses from extreme weather events cost the country 1 to 3 percent of gross domestic product each year. As China's economy continues to grow, its exposure to weather-related hazards is expected to heighten, especially without policies to limit building in hazardous areas such as floodplains and alleviate non-climate pressures such as overuse of freshwater resources. Effective risk management policies and investments are crucial to reducing the sensitivity and increasing the resilience of the country to extreme weather, climate variability, and long-term climate change.